Automation in tender evaluation in construction industry to increase procurement planning efficiency, transparency, quality bidding and focus on sustainability factors - Wasiew, Qudrati Al (Brac University, 2022)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.